Deskripsi Kesiapan Masuk Sekolah Calon Siswa SD di Deli Serdang - Hapni Madini; Atika Azharo; Dina Rahmah Wati (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2025)
Preparing for primary school is an important phase in a child's educational development. This study aimed to analyze the relationship between strengths and difficulties identified through the Strength and Difficulties Questionnaire (SDQ) with school entry readiness in prospective elementary school students in Deli Serdang Regency. The study involved data collection using the SDQ which covers five main domains: emotional problems, behavioral problems, hyperactivity, relationships with peers, and pro-social behavior. The results showed that children with high scores on pro-social behavior and low scores on behavioral problems had better readiness to adapt to the school environment. In contrast, high scores on emotional problems and hyperactivity indicate potential obstacles in the adaptation process. This study confirms the importance of using the SDQ as an evaluation tool to identify areas in need of intervention, thereby supporting children's optimal transition to formal education. The implications of the results of this study can serve as a reference for parents, teachers, and policy makers in developing strategies that support children's readiness to enter primary school. Keywords: SDQ, School Readiness